On the mechanisms of the internalization of S4(13)-PV cell-penetrating peptide - Mano, Miguel (2005)
Cell-penetrating peptides have been shown to translocate across eukaryotic cell membranes through a temperature-insensitive and energy-independent mechanism that does not involve membrane receptors or transporters. Although cell-penetrating peptides have been successfully used to mediate the intracellular delivery of a wide variety of molecules of pharmacological interest both in vitro and in vivo, the mechanisms by which cellular uptake occurs remain unclear. In the face of recent reports demonstrating that uptake of cell-penetrating peptides occurs through previously described endocytic pathways, or is a consequence of fixation artifacts, we conducted a critical re-evaluation of the mechanism responsible for the cellular uptake of the S4(13)-PV karyophilic cell-penetrating peptide. We report that the S4(13)-PV peptide is able to accumulate inside live cells very efficiently through a rapid, dose-dependent and non-toxic process, providing clear evidence that the cellular uptake of this peptide cannot be attributed to fixation artifacts. Comparative analysis of peptide uptake into mutant cells lacking heparan sulphate proteoglycans demonstrates that their presence at the cell surface facilitates the cellular uptake of the S4(13)-PV peptide, particularly at low peptide concentrations. Most importantly, our results clearly demonstrate that, in addition to endocytosis, which is only evident at low peptide concentrations, the efficient cellular uptake of the S4(13)-PV cell-penetrating peptide occurs mainly through an alternative, non-endocytic mechanism, most likely involving direct penetration across cell membranes